Main Concepts in the Control of Swarm Drones - Ismayilov, I.M.; Mirzayev, I.R. (Herald of Azerbaijan Engineering Academy, 2025)
Unmanned Aerial Vehicles have brought new opportunities in the security, efficiency and precision of aerial operations. Their application areas include military, search and rescue operations, perimeter security, environmental monitoring etc. The UAVs have proved to be useful in many operations and lately they are being utilized as groups to extend their capabilities. Swarm drones utilize the drones as a group of nodes that can communicate and collaborate with each other to realize the given mission. The use of drones as a group helps to overcome the problem of single point of failure while improving efficiency and scalability. Although swarm drones offer so many advantages, there are several challenges to be addressed to enable successful utilization of them. Depending on the UAV type, a corresponding network architecture, formation strategy and formation control method should be provided. To apply swarm drones on a large scale there are still some areas that need to be researched and improved. The paper aims to realize qualitative bibliometric analysis in the topic, cover main technical concepts and do comparative analysis of different approaches in different scenarios.